2020
DOI: 10.1021/acs.chemmater.0c01581
|View full text |Cite
|
Sign up to set email alerts
|

Sb2S3/TiO2 Heterojunction Photocathodes: Band Alignment and Water Splitting Properties

Abstract: Antimony sulfide (Sb2S3) is a promising light absorbing semiconductor for photovoltaic applications, though it remains vastly unexplored for photoelectrochemical water splitting. Sb2S3 was synthesized by a simple sulfurization of electrodeposited antimony metal at relatively low temperatures (240-300°C) with elemental sulfur. Using a TiO2 buffer layer and a platinum cocatalyst, photocurrent densities up to ~ 9 mA cm-2 were achieved at-0.4 V vs. RHE in 1 M H2SO4 under one sun illumination. Using XPS band alignm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…This suggests that there is a large degree of charge transfer upon contact, which increases the VBO (and CBO) from the natural value. The existence of a clifflike offset is supported by the observation of a similar alignment for Sb 2 S 3 and TiO 2 reported elsewhere …”
Section: Discussionsupporting
confidence: 84%
“…This suggests that there is a large degree of charge transfer upon contact, which increases the VBO (and CBO) from the natural value. The existence of a clifflike offset is supported by the observation of a similar alignment for Sb 2 S 3 and TiO 2 reported elsewhere …”
Section: Discussionsupporting
confidence: 84%
“…To achieve a high STH conversion efficiency, the light absorbing photoelectrode materials should be capable of absorbing sufficient sunlight, transporting to the electrolyte efficiently, and remaining long-term stable without photocorrosion [4] . To date, numerous semiconductors have been developed for PEC solar hydrogen production, such as Si [5] , SiC [6] , Cu 2 O [7] , CdTe [8] , Cu-chalcogenides [9][10][11][12] and Sb-chalcogenides [13,14] . However, the continuous exploration of earth-abundant and low-cost candidates are still getting growing concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al grew narrow band gap ZnFe 2 O 4 leaves on TiO 2 trees by atomic layer deposition and a boosted PEC water splitting ability was also achieved. With regard to electron–hole separation, heterostructure construction is an efficient approach. It was demonstrated that a facet heterojunction structure between rutile TiO 2 nanorods and different facets of TiO 2 nanosheets can promote charge transfer and prolong the lifetime of photogenerated electrons . Prabhakar et al also reported that Sb 2 S 3 /TiO 2 heterojunction photocathodes could achieve a high photocurrent density with good band alignment .…”
Section: Introductionmentioning
confidence: 99%
“…With regard to electron–hole separation, heterostructure construction is an efficient approach. It was demonstrated that a facet heterojunction structure between rutile TiO 2 nanorods and different facets of TiO 2 nanosheets can promote charge transfer and prolong the lifetime of photogenerated electrons . Prabhakar et al also reported that Sb 2 S 3 /TiO 2 heterojunction photocathodes could achieve a high photocurrent density with good band alignment . Therefore, modification of TiO 2 with a narrow band gap semiconductor to construct a heterostructure would be promising to extend the light absorption range and facilitate charge separation for improving the PEC water splitting performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation